Culture and healthy lifestyles: a qualitative exploration of the role of food and physical activity in three urban Australian Indigenous communities. (14th June 2017) - Crowe, Ruth; Stanley, Rebecca; Probst, Yasmine; McMahon, Anne
Abstract: Objective: 1) To explore the links between Indigenous Australian children's perspectives on culture, and healthy lifestyle behaviours. 2) To provide insight into how to approach the development of a health intervention targeting lifestyle behaviours in Australian Indigenous children. Methods: Seven semi‐structured focus groups sessions were conducted with Australian Indigenous children aged 5–12 years living on the South Coast of New South Wales. Audio‐recordings were transcribed and thematic analyses were conducted and related to principles of grounded theory. Results: Participants had connections to aspects of Australian Indigenous culture that were embedded in their everyday lives. Healthy lifestyle behaviours (such as healthy eating and physical activity) were found to be interconnected with Australian Indigenous culture and positive emotional wellbeing was identified as an important outcome of connecting Australian Indigenous children to cultural practices. Conclusion: Understanding the importance of culture and its role in healthy lifestyles is critical in the development of health interventions for Indigenous populations. Implication: Health interventions embedded with Australian Indigenous culture may have potential to improve physical and emotional health within Australian Indigenous communities. However, it is unlikely that a 'one size fits all' approach to health interventions can be taken.